Impacting Employee Performance by Supporting Intrapreneurial Activities - Galit Klein; Batia Ben-Hador (Administrative Sciences)
Extensive empirical findings support the idea that intrapreneurial activity benefits employees, organizations, and society. Grounded in Self-Determination Theory (SDT), this paper analyzes the mediating role of intrapreneurial behaviors in the relationship between organizational support for intrapreneurship and employee performance and the moderating role of intra-organizational social capital (ISC) in the relationship between organizational support and intrapreneurial behaviors. Hypotheses were tested using regression analyses via Hayes’ PROCESS macro, allowing for the assessment of moderation–mediation effects. Data were collected from 617 employees across various Israeli organizations using a structured questionnaire. The results indicate that intrapreneurial behaviors are positively associated with employee performance. Additionally, organizational support is indirectly related to performance through intrapreneurial behaviors. This indirect effect is stronger when ISC levels are high, indicating that ISC amplifies the positive impact of organizational support on intrapreneurial behaviors. The findings highlight the importance of both organizational context and individual differences in fostering intrapreneurial activity and enhancing employee performance.